Analysis of risk factors for the progression and prognosis of connective tissue disease-associated interstitial lung disease - Ting Zhao; Fu-an Lin; Hongpu Chen (Archives of Rheumatology, 2023)
Objectives: This study aimed to investigate the risk factors of lung progression in patients with connective tissue disease-associated interstitial lung disease (ILD). Patients and methods: A total of 91 ILD patients (28 males, 63 females; mean age: 54.9±11.3 years; range, 30 to 77 years) were included in the prospective follow-up study conducted throughout 2020. They were divided into progressors (n=27) and nonprogressors (n=64) according to whether the pulmonary disease progressed during a six-month follow-up period. The clinical data of the two groups were analyzed, and a logistic regression model was constructed to analyze the risk factors of the progression of ILD in all patients. Results: Univariate analysis revealed significant differences (p<0.05) between the two groups in smoking history, serum ferritin, FVC% (the percentage of forced vital capacity), DLCO% (the percentage of diffusion capacity for carbon monoxide), and computed tomography involvement range. Further application of a logistic regression model revealed that increased serum ferritin level was an independent risk factor for ILD progression (odds ratio=1.002, 95% confidence interval: 1.000-1.003, p=0.004). The optimal critical value of serum ferritin was 303.25 ng/mL, the sensitivity and specificity were 81.5% and 54.7%, respectively, and the area under the curve was 0.747. Conclusion: The level of serum ferritin may be an independent predictor for ILD progression.